2008
DOI: 10.1186/1471-2180-8-155
|View full text |Cite
|
Sign up to set email alerts
|

Hfq regulates the expression of the thermostable direct hemolysin gene in Vibrio parahaemolyticus

Abstract: Background: The hfq gene is conserved in a wide variety of bacteria and Hfq is involved in many cellular functions such as stress responses and the regulation of gene expression. It has also been reported that Hfq is involved in bacterial pathogenicity. However, it is not clear whether Hfq regulates virulence in Vibrio parahaemolyticus. To evaluate this, we investigated the effect of Hfq on the expression of virulence-associated genes including thermostable direct hemolysin (TDH), which is considered to be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…The recent reports of the role of Hfq in virulence in the human pathogen Vibrio parahaemolyticus as well as in the fish pathogen Vibrio alginolyticus underscore the likeliness of the importance of sRNAs in virulence in these other species (Nakano et al 2007(Nakano et al , 2008Liu et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The recent reports of the role of Hfq in virulence in the human pathogen Vibrio parahaemolyticus as well as in the fish pathogen Vibrio alginolyticus underscore the likeliness of the importance of sRNAs in virulence in these other species (Nakano et al 2007(Nakano et al , 2008Liu et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we reported ∆Hfq V. parahaemolyticus had a slower growth rate than the parental strain (Nakano et al, 2008). These indicated that the growth rate and anti-oxidative capability against H 2 O 2 were dependent on different functions.…”
Section: Discussionmentioning
confidence: 88%
“…a reduced growth rate and higher production of thermostable direct hemolysin (TDH) compared with that of the parental strain, which indicated that Hfq had an effect on the growth and was associated with the production of TDH in V. parahaemolyticus (Nakano et al, 2008).…”
mentioning
confidence: 99%
“…Deletions of the vp0920 and vp2911 genes were generated by homologous recombination as reported previously (25). Briefly, ϳ500-bp fragments immediately upstream and downstream of the gene of interest were amplified by PCR using primer pairs (Table 2).…”
Section: Methodsmentioning
confidence: 99%